(untitled) (Journal of Plant Disease Sciences, 2023)
Chickpea is the world’s second most important legume, and it can be nodulated with a variety of rhizobial species to generate root nodules. The current study investigated the isolation, cultural, and biochemical characterization of several strains of root nodulating bacteria from different locations of Yavatmal districts. The serial dilution approach was used for isolation. Bacterium Mesorhizobium is a gram- negative, aerobic, non-spore producing, motile rods with circular, convex, whitish pink, and glistering colonies with an entire edge. The biochemical characterization of five different strains of bacteria revealed that the catalase, methyl red, urease, and triple sugar iron and citrate utilization test yielded positive results. Based on morphological, biochemical, and physiological characters most of the characteristics were found like the Mesorhizobium spp. The physical and biochemical properties of five different isolates of bacteria were analyzed to determine their taxonomic position, and the authentication test revealed that the strain of rhizobium bacteria is Mesorhizobium spp.